The End of Imperial Town Planning in Upper Canada - Reid, Richard (Urban History Review / Revue d'histoire urbaine, 1990)
In the years following the War of 1812 imperial officials, for reasons of strategic and domestic concern, founded a series of towns along the route from Kingston to the Ottawa River. Three of the "military settlements", Perth, Richmond and Lanark, reflected aspects of an earlier town planning tradition in Upper Canada and enjoyed a limited success as the nuclei for a certain type of society A fourth town, By town, was founded with less planning but quickly became the major urban centre in the Ottawa Valley Conflicting aims of the military planners and the towns civilians made By town's experience very different from the other three towns.